Effect of gypsum and cement content on unconfined compressive strength of soft sediment. Issue 3 (16th March 2021) - Janbaz, Masoud; Iacobucci, Lauren; Francisco, Kelly; Miskewitz, Robert; Kitazume, Masaki; Maher, Ali
ABSTRACT: This study investigates the impact of gypsum and Portland cement as binding agents on the stabilization of soft sediment. Eight combinations of gypsum and Portland cement were studied to identify the optimum gypsum content for a total binder content of 8% (by wet weight of sediment). Samples were cured for 7 and 28 days at high and low temperatures (4°C and 20°C). Unconfined compressive strength and moisture content were measured to assess the effectiveness of each mixing condition on soil engineering properties. The results of the study show that the inclusion of gypsum in mixtures of Portland cement and soft sediment can significantly enhance the strength gain of stabilized sediment. The optimum mixture was identified as 1.4% gypsum and 6.6% Portland cement (of the total mass of sediment). This combination produced a 50% increase in strength when compared to a standard 8% Portland cement mixture.